An unchanging reservoir continually providing new variants: an updated review of the case of influenza virus. - Frost, Eric H. (CIENCIA ergo-sum, 2017)
Influenza virus infection usually provokes a strain-specific inmunity that prevents the same virus strain from causing epidemics in two successive years without at least minor antigenic variation. Influenza in waterfowl avoids this rule and constitutes an unchanging reservoir because of the annual production of large numbers of immunologically-naive offspring that may be contaminated by virus preserved from the previous year in frozen lakes. Humans are usually infected when a variant of the preceding year's strain spreads world-wide. This process of gradual antigenic change, called drift, is cumulative and results in considerable antigenic change over a period of years until a new strain appears. New strains derivefrom the waterfowl reservoir, probably after reassortment in swine which are susceptible to both avian and human influenza viruses. This change, termed shift, results in highly virulent pandemics. The change in animal husbandry brought about by modern farming techniques may also allow swine to play an important role as a reservoir in addition to their recognized role as a mixing vessel. This review presents the process of variation and modification of viruses from virulent epidemic to benign nuisance drawing examples from influenza virus infections of man, of animals, and of birds.